2009
DOI: 10.1177/1045389x08102265
|View full text |Cite
|
Sign up to set email alerts
|

Approximate SIF of Mode-I Crack Closure in Matrix by Knotted SMA Fiber

Abstract: In this article, a theoretical model is proposed on closure of mode-I crack in matrix embedded with prestrained shape memory alloy (SMA) fiber as an actuator. To overcome fiber de-bonding in matrix, two knots are made on a SMA fiber. By shape memory effect with the rise in temperature, the SMA fiber generates a couple of recovery forces acting on the matrix at the two knots. This couple of recovery forces may restrain opening of the mode-I crack. Based on Tanaka constitutive law on SMA fiber and complex stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Many researchers have employed activated SMA wires in cracked polymeric resins to prevent crack initiation and propagation. [25][26][27][28][29][30][31][32][33] Ciampa et al 32 manufactured carbon fiber-reinforced polymers tufted in the thickness direction by SMA wires and evaluated their delamination resistance using double cantilever beam (DCB) samples. The finite element analysis and test results revealed that complete crack closure could be achieved by activating the SMAs.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have employed activated SMA wires in cracked polymeric resins to prevent crack initiation and propagation. [25][26][27][28][29][30][31][32][33] Ciampa et al 32 manufactured carbon fiber-reinforced polymers tufted in the thickness direction by SMA wires and evaluated their delamination resistance using double cantilever beam (DCB) samples. The finite element analysis and test results revealed that complete crack closure could be achieved by activating the SMAs.…”
Section: Introductionmentioning
confidence: 99%